(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
Chitosans are naturally occurring biologically safe and non-toxic polymer of polysaccharides. In the present study, Chitosan [(1-4) 2-amino-2-deoxy-β-D-glucan] was extracted from the exoskeleton of Black Tiger (Penaeus monodon) shrimp shells by alkaline deacetylation of chitin. Three different chitosan extracts, coded as Chito A (3.33% w/w), Chito B (4.01% w/w) and Chito C (3.45% w/w) were extracted using 3%, 4% and 5% w/v concentrations of HCl as decalcifiers respectively. Physicochemical properties such as appearance, odor, insolubility and pH of all the extracts were found to comply with the compendial specifications of pharmaceutical grade chitosan. Qualitative identification of the samples was carried out using Infrared (IR) spectroscopy. Major peaks of the extracts matched with reference IR spectrum of standard chitosan. Extracted chitosans were found lacking cytotoxicity in brine shrimp lethality bioassay. All the extracts showed strong antioxidant activity in DPPH free radical scavenging assay and the IC50 values were found to be 37 ± 2 μg/mL (Chito A), 35 ± 1 μg/mL (Chito B) and 30 ± 2 μg/mL (Chito C) while the standard antioxidant Quercetin showed an IC50 value of 15 ± 2 μg/mL. Key words: Chitosan; Black Tiger (Penaeus monodon) shrimp shells; deacetylation of chitin; IR spectroscopy; cytotoxicity; DPPH; free radical scavenging. DOI: 10.3329/sjps.v2i2.5821 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 27-30